Enhancing Children's Science Literacy Through the Use of Problem Based Learning Model - Retnaningsih, Lina Eka; Yuliastrin, Adisti; Sari, Dwi Lyna; Yonantha, Ferri (JCE (Journal of Childhood Education), 2024)
This study is prompted by the low PISA scores in reading, math and science literacy. Science literacy is crucial to develop early when children are still in the foundation phase. The current Merdeka curriculum supports the development of science literacy. KB Tunas Harapan 1 Tunggunjagir rarely develops children's science literacy so that the phenomenon of low children's scientific literacy is found. The purpose of this study was to describe the process and results of applying the problem-based learning model to enhance children's science literacy skills at KB Tunas Harapan. This study is a classroom action research referring to the Kemmis and Mc Taggart model which consists of the stages of planning, action, observation and reflection. This research was conducted in 2 cycles where each cycle consisted of 6 meetings. The data were analyzed qualitatively and quantitatively. The results showed an increase in children's science literacy skills through the implementation of the problem-based learning model can be evidenced in the average pre-intervention score of 17.38 then increased in cycle I to 33.63 And in cycle 2 the average increase into 46.03 from the maximum score of 56.